2015
DOI: 10.3832/ifor1060-008
|View full text |Cite
|
Sign up to set email alerts
|

Does higher owner participation increase conflicts over common land? An analysis of communal forests in Galicia (Spain)

Abstract: © iForest -Biogeosciences and Forestry IntroductionIn a modern sense, public participation in devising forest management is voluntary. Within public participation processes, people, individually or in organized groups, can exchange information, express opinions and articulate interests with the aim of influencing the final result in decision making (ILO 2000, Aasetre 2006, Atmis et al. 2007. It is both an opportunity and a need for today's society, as it is a useful tool to avoid conflicts, share information a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 76 publications
(111 reference statements)
0
10
0
4
Order By: Relevance
“…É moi importante crear unha sociedade consciente e informada dos riscos asociados ao lume, e autoprotexida, pero que ao mesmo tempo conte co lume como un elemento máis do sistema socio-ecolóxico no que está inmersa, que se sinta concernida co problema e contribuínte activa nas decisións tomadas polos xestores públicos (Everett 2002, Tábara et al 2003, Hernando et al 2012, McCaffrey et al 2013, Marino et al 2014, Tedim et al 2016. É preciso, polo tanto, facilitar a participación social e o consenso político sobre o tema porque, en definitiva, se trata dun problema colectivo complexo, que ten as súas raíces na nosa sociedade e lle corresponde a ela o principal papel na súa resolución (Tedim et al 2015e 2016, Bruña e Marey 2013e 2017, Marey et al 2015.…”
Section: Algunhas Consideracións E Propostas De Adaptación Ao Novo Escenariounclassified
“…É moi importante crear unha sociedade consciente e informada dos riscos asociados ao lume, e autoprotexida, pero que ao mesmo tempo conte co lume como un elemento máis do sistema socio-ecolóxico no que está inmersa, que se sinta concernida co problema e contribuínte activa nas decisións tomadas polos xestores públicos (Everett 2002, Tábara et al 2003, Hernando et al 2012, McCaffrey et al 2013, Marino et al 2014, Tedim et al 2016. É preciso, polo tanto, facilitar a participación social e o consenso político sobre o tema porque, en definitiva, se trata dun problema colectivo complexo, que ten as súas raíces na nosa sociedade e lle corresponde a ela o principal papel na súa resolución (Tedim et al 2015e 2016, Bruña e Marey 2013e 2017, Marey et al 2015.…”
Section: Algunhas Consideracións E Propostas De Adaptación Ao Novo Escenariounclassified
“…Estos resultados redundan en el papel clave del abandono del rural identificado en trabajos sobre la relación entre distintos factores socioeconómicos con el tipo de manejo forestal practicado en las comunidades de montes vecinales mancomunadas gallegas (Marey Pérez et al, 2014). Estos autores apuntan, en línea con nuestras aportaciones, que el abandono de los terrenos y la inexistencia de procesos decisorios sobre el manejo del monte, que sean capaces de integrar la diversidad creciente de demandas realizadas, tienen el riesgo asociado, de cara al futuro, de desplazar aquellas motivaciones de tipo emocional o intrínsecas que ayudan a explicar el mantenimiento de la actividad forestal entre muchas personas pequeñas propietarias, y en las que el sentimiento de lugar se sostiene.…”
Section: Bloqueo Y Refuerzo Del Equilibrio: La Percepción De Irreversibilidadunclassified
“…La cultura define las condiciones para la reproducibilidad de modos de vida, la compatibilidad de las plantaciones forestales con otros usos y las posibilidades de satisfacción material y emocional de las comunidades (Jasper, 2017), incluidos los modelos de gestión forestal y el tipo de conflictos y respuestas ante estos (Marey-Pérez, Díaz-Varela y Calvo González, 2014). La integración de la cultura en los estudios de la acción colectiva sirve de puente con los análisis de cambio social, al recoger significados compartidos basados en la identidad que atraviesan las dinámicas de la acción colectiva (van Zomeren y Louis, 2017).…”
Section: Introductionunclassified
“…Galicia is a province in northwestern Spain characterized by a high relative percentage of its total forest area, which represents over 60% of its surface area and accounts for 11% of the total forest area of Spain (Marey-Perez, Diaz-Varela & Calvo-Gonzalez, 2014), the stock of timber being more than 133 million m 3 , accounting for 19% of the total Spanish timber reserve and representing nearly half of the Spanish production of timber, with 98% of the forests being privately owned and the remaining 2% owned by the public sector (Caballero, 2015).…”
Section: Forestry Sector Of Galicia (Spain)mentioning
confidence: 99%
“…Some studies on the timber industry of Argentina and Latin America were found (Martos, F-Jar-dón & Figueroa, 2008;F-Jardón & Martos, 2014;F-Jardón & Silva, 2017) but none on the Spanish area, as far as intellectual capital is concerned. The studies on Spain were mainly related to forest management (Carvalho-Ribeiro & Lovett, 2011) or ownership issues (Marey-Perez, Diaz-Varela & Calvo-Gonzalez, 2014). There are also works that analyze this impact in Latin American countries.…”
Section: Introductionmentioning
confidence: 99%